Exploring dimensional quilt art : stitch, fold, embellish - Barnes, C. J. (C. June) (Interweave, 2012)
"Exploring Dimensional Quilt Art takes quilters above and beyond the surface with innovative techniques for raising surfaces and creating three-dimensional fabric structures. Discover how to incorporate these expressive effects into your quilting, from the simplest textured quilt to elaborate twisted and embellished structures, including vessels and hanging installations. Popular quilt artist C. June Barnes explores various folding, gathering, pleating, stuffing, padding, shrinking, and layering techniques. You'll also achieve intriguing depths to your quilts when you learn how to manipulate the surface of the quilted plane by constructing objects through various means. Journey through this one-of-a-kind guide and learn how to create your own trendy effects while discovering the secrets of how these sometimes impossible-looking structures are created. Invaluable technical construction tips and a wealth of inspiration from Barnes and some of the world's leading quilt artists offer you a complete exploration. This book is the essential reference guide for a broad spectrum of quiltmakers. "--